Treatment of Hepatoblastoma With Drug-eluting Bead Transarterial Chemoembolization in a 13-Month-Old Infant: A Case Report and Review of the Literature. Issue 1 (January 2021) - Hoyer, Matthew; Goli, Rakesh; Barnett, Katherine K.; Raabe, Eric H.; Hong, Kelvin
Abstract : Background: Prior reports have shown the utility of conventional lipiodol-based transarterial chemoembolization in hepatoblastoma. The authors describe the first reported case of hepatoblastoma treated with drug-eluting bead transarterial chemoembolization (DEB-TACE). Observations: An 11-month-old infant presented with hepatoblastoma measuring 14.3 cm. A trial of cisplatin chemotherapy followed by sequential DEB-TACE to the tumor's feeding vasculature reduced the mass to 5.3 cm. The patient tolerated both sessions of DEB-TACE without any major complication. Having demonstrated adequate disease control, the patient then underwent successful liver transplantation. Conclusion: This report provides promising evidence for the treatment of hepatoblastoma with DEB-TACE.